1986
DOI: 10.1055/s-2008-1043396
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Seizure Disorder in Children with Acquired and Congenital Hydrocephalus

Abstract: 202 cases of children with shunted hydrocephalus of congenital or acquired origin were studied and the incidence of seizure disorder was found to be 39%. However in only 17% of cases was the seizure disorder found to be persistent. Focal seizures were rarer than expected. If focal seizures were present they did not appear to be related to shunt site. 9.4% of children suffered an episode of status epilepticus. A large number of incidents of seizures could be shown to have a specific precipitant, usually CSF inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
3

Year Published

1988
1988
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
1
18
3
Order By: Relevance
“…The most important shunt-related variables in this study are shunt complications (infection) and shunt revisions. In contrast to some studies that did not find any relation [1,3,4,7,10,22], others showed that shunt complications and shunt revisions increase the incidence of seizures in shunted patients [5,6,11,21,22,23,24] so that shunt complications are considered to be responsible for large numbers of seizures [22]. Bourgeois et al [5] showed that the incidence of seizures was higher in patients with shunt complications.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…The most important shunt-related variables in this study are shunt complications (infection) and shunt revisions. In contrast to some studies that did not find any relation [1,3,4,7,10,22], others showed that shunt complications and shunt revisions increase the incidence of seizures in shunted patients [5,6,11,21,22,23,24] so that shunt complications are considered to be responsible for large numbers of seizures [22]. Bourgeois et al [5] showed that the incidence of seizures was higher in patients with shunt complications.…”
Section: Discussioncontrasting
confidence: 41%
“…Also, a family history was not a significant risk factor in this study as in the report of Noetzel and Blake [4]. Some studies failed to find a role for etiology of hydrocephalus in seizure development in shunted patients [10,20,21,22] while the majority of authors have shown that the frequency of seizures in spina bifida and myelomeningocele patients is much lower than the risk in patients with hydrocephalus secondary to hemorrhage, trauma, or infection [3,4,5,7,11,23,24,25]. Heinsbergen et al [23], in a retrospective study of 119 shunted patients, showed that among etiologic factors, the odds ratio of developing seizure is 2.5 for hemorrhage and 2.3 for infection while it is 0.3 for spina bifida.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Mental retardation was diagnosed four times as frequently in children with seizures [18]. Children with IQ scores of 70 or below were more likely to experience seizures than were children with normal intelligence [22], and furthermore in children with meningomyelocele mental retardation was statistically more common when associated with seizures, regardless of the presence or absence of hydrocephalus [17].…”
Section: Discussionmentioning
confidence: 99%
“…Shunt infections are associated with higher rates of revision, recurrence of infection, ventriculitis, meningitis, and encephalitis, and often with greater mortality rates (Winston, Ho & Dolan 2013). Complications include loss of intelligence quotient (IQ) and increased seizure risk, both of which occur via mechanisms that have yet to be defined (Vinchon, Dhellemmes 2006, Sato et al 2001, Stellman, Bannister & Hillier 1986, Chadduck, Adametz 1988). This may be due to neuronal death as a direct result of infection or may be a consequence of inflammation within the central nervous system (CNS) due to the infection.…”
Section: Introductionmentioning
confidence: 99%